Humic acid composite repairing material for coal chemical polluted site and preparation method of humic acid composite repairing material
By preparing a humic acid composite repair material rich in functional groups, the problem of soil pollution in coal chemical pollution sites has been solved, the soil structure improvement and repair efficiency have been improved, and the ability to efficiently adsorb heavy metals and organic pollutants is achieved.
Patent Information
- Application Number
- CN202411923230.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The soil pollution degree of coal chemical pollution sites is high, the pollution range is wide, the pollution depth is deep, and the pollution duration is long. The existing humic acid materials are unclear in grades and components, and the basic research on modification is insufficient, resulting in insufficient application effect of soil restoration.
A humic acid composite repair material is prepared by mixing and filtration of dilute alkali solution and acid solution to obtain a humic acid solution rich in functional groups, and then dried and ground, combining sodium pyrophosphate and acyclic carboxylic acid to form a humic acid composite material that is easy to adsorb heavy metals.
Effectively improve soil structure and quality, significantly improve soil restoration efficiency, can effectively adsorb heavy metals and organic pollutants, reduce the effective content of heavy metals in the soil, and reduce bioaccumulative risks.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of soil remediation materials, and in particular relates to a humic acid composite remediation material for coal chemical industry polluted sites and a preparation method thereof. Background Art
[0002] The soil problems of coal chemical pollution sites are mainly organic pollution and heavy metal pollution. These pollutants usually come from wastewater and solid waste in the coal chemical production process. Due to the complex composition and high concentration of toxic and hazardous substances in chemical production emissions, they are easy to penetrate into the deep soil layer, causing comprehensive soil pollution. The soil around chemical enterprises has been polluted by chemical wastewater and waste gas for a long time, which has seriously affected the soil in the surrounding environment. Due to the toxic substances in wastewater and waste gas discharged during chemical production penetrate into the deep soil layer, the soil pollution range reaches as deep as the groundwater layer. Due to the serious accumulation of toxic substances in wastewater and waste gas discharged in the chemical production process, the residual period of soil pollution is long. At present, due to the combined effects of rural township enterprises, agricultural production, sewage irrigation, fertilizers and pesticides, agricultural films and other factors, the degradation of soil environmental quality and ecological functions caused by soil pollution has become one of the main threats to soil function degradation.
[0003] In order to solve this problem and avoid affecting the physical and chemical properties of the soil, microbial communities, and enzyme activity, the field generally uses natural organic matter humic acid for soil remediation. Humic acid has diverse structures, multiple functional groups, large molecules, and wide distribution. It has a variety of physical and chemical properties, such as solubility, acidity, ion exchange, and complexation (chelation). It can efficiently adsorb heavy metals, organic pollutants, radioactive pollutants, and other contaminated soils.
[0004] However, the existing humic acid materials are not clearly classified and composed. They are commercially divided into coal-based humic acid and biochemical humic acid. Coal chemical industry divides coal-based humic acid into yellow humic acid (fulvic acid), brown humic acid and black humic acid (humin), and also into water-soluble humic acid, insoluble humic acid, large molecule humic acid and small molecule humic acid, etc. However, the industry has insufficient basic research on humic acid modification, and even directly uses unactivated weathered coal and lignite for modification, resulting in insufficient soil remediation application effect, or even negative effects, and unable to solve the problems of humic acid degraded soil improvement, heavy metal and organic pollution remediation, etc. Summary of the invention
[0005] Based on the above content, in order to solve the problems of high soil pollution degree, wide pollution range, deep pollution depth and long pollution duration in coal chemical pollution sites, the present invention proposes a humic acid composite remediation material for coal chemical pollution sites and a preparation method thereof.
[0006] The objects of the present invention are:
[0007] 1. It can effectively improve soil structure and quality;
[0008] 2. It can effectively improve the efficiency of soil remediation.
[0009] To achieve the above objectives, the present invention adopts the following technical solutions.
[0010] A method for preparing a humic acid composite repair material for coal chemical pollution sites,
[0011] The method comprises:
[0012] 1) Mix the raw materials, alkali solution and phosphide evenly, take the supernatant after standing, add acid solution to adjust the pH value of the system, and obtain humic acid solution by suction filtration;
[0013] 2) Drying step 1) The solid obtained by the operation is allowed to stand, and an acid solution is added to mix evenly, filtered, washed, corroded by adding a strong acid, filtered again, washed, and dried to obtain a substrate;
[0014] 3) The organic raw material, emulsifier and solvent are heated, and while stirring, a mixture of acyclic carboxylic acid and humic acid solution is added, and an initiator is added. After a thermal reaction, the base material is added while hot and mixed evenly, and the humic acid composite repair material is obtained after drying and grinding.
[0015] As a preference,
[0016] Step 1) The raw material is low-quality coal;
[0017] The low-quality coal is lignite and / or weathered coal and / or coal;
[0018] The alkali solution is a 0.1-0.5 mol / L NaOH aqueous solution, and its dosage is 5.0-10.0 mL / g raw material;
[0019] The phosphide is sodium pyrophosphate, and its usage is 0.05-0.10 g / g raw material.
[0020] As a preference,
[0021] Step 1) The acid solution is a 0.1-0.5 mol / L HCl aqueous solution, and its dosage is 1.0-1.5 mL / g raw material.
[0022] As a preference,
[0023] Step 2) The cleaning is to wash the product with distilled water until it is neutral;
[0024] Step 2) The strong acid is a 35-45 wt% HF aqueous solution, and the amount used is 5-10 mL / g of the solid obtained in step 1).
[0025] As a preference,
[0026] Step 3) the organic raw materials are butyl acrylate and cyclohexane;
[0027] The mass ratio of butyl acrylate to cyclohexane is 1:(0.2-0.3);
[0028] The emulsifier is sorbitan tristearate, and its dosage is 0.01-0.05 g / g organic raw material;
[0029] The solvent is acetone, and the amount thereof is 15 to 25 mL / g of organic raw material;
[0030] Step 3) The temperature is raised to 50-60°C.
[0031] As a preference,
[0032] Step 3) in the mixture of the acyclic carboxylic acid and the humic acid solution:
[0033] The acyclic carboxylic acid is acrylic acid;
[0034] The acyclic carboxylic acid and humic acid solution are prepared in a volume ratio of 1: (0.5-0.7) and mixed evenly.
[0035] As a preference,
[0036] Step 3) The initiator is potassium persulfate, and the amount thereof is 0.05-0.1 g / g organic raw material;
[0037] Step 3) The thermal reaction is carried out at 80-90°C for 2-5 hours.
[0038] As a preference,
[0039] Step 3) The substrate is added in an amount of 0.9 to 1.1 g per gram of organic raw material.
[0040] As a preference,
[0041] Step 3) The grinding is followed by passing through a 60-100 mesh sieve.
[0042] A humic acid composite repair material for coal chemical industry polluted sites.
[0043] Soil pollutants in coal chemical contaminated sites include polycyclic aromatic hydrocarbons (benzo[a]pyrene, fluoranthene, pyrene, etc.), chlorinated hydrocarbons (1,2-dichloropropane, 1,2,3-trichloropropane, etc.), organic pollutants (chloroform, bis(2-chloroisopropyl) ether, etc.) and a large number of heavy metal pollutants. These pollutants have a serious negative impact on the soil, and among them, the removal of heavy metal pollutants is particularly difficult and costly. In order to repair coal chemical contaminated sites, the present invention provides a humic acid composite repair material for coal chemical contaminated sites, and a preparation method of the material.
[0044] According to the research of those skilled in the art, insoluble humic acid has a significant passivation and repair effect on heavy metals in soil. The technical solution of the present invention is based on the modification of insoluble humic acid, and the raw materials can be obtained from coal chemical plants, which greatly reduces the preparation cost. The present invention first obtains humic acid (palmitic humic acid), fulvic acid, etc. rich in functional groups such as carbonyl, carboxyl, and ether oxygen groups by leaching acid with dilute alkali solution and acid solution assisted precipitation. The bound humic acid that is difficult to dissolve in water and soluble in water is complexed into humic acid salts that are easily soluble in water, and cooperates with sodium pyrophosphate to significantly increase the amount of humic acid extraction. It was found through experiments that the effect of "NaOH solution dissolution and HCl solution precipitation" is better than "KOH solution dissolution and HNO3 solution precipitation". Considering that the cation of substances such as sodium pyrophosphate is sodium, the present invention uses NaOH solution for alkali solution dissolution. HNO3 solution has a strong oxidizing effect, can react with functional groups, and degrade humic acid macromolecules into small molecules. Moreover, since the solution is rich in divalent metal ions, the present invention avoids the use of sulfuric acid, otherwise precipitation will be formed, reducing the purity of the humic acid product. However, if the pH value of acid precipitation is too high, other impurities will dissolve and affect the purity of humic acid.
[0045] The active groups of humic acid can chelate with small molecules or complex with metal ions. The soluble heavy metal ions in the soil undergo exchange reactions with humic acid, which can reduce the soil base content. +, neutralize alkaline substances in the soil and reduce soil alkalinity. Functional groups such as aldehydes and carboxyls in humic acid react with cations in the soil to form humates, forming a buffer system for the mutual conversion of humic acid and humate. However, the unmodified humic acid components are complex and the complexing ability for metal ions is insufficient, resulting in a large amount of phosphorus and iron and aluminum in the soil to form precipitation and lose activity. In alkaline soils, the effect of humic acid chelating or complexing iron and aluminum is insufficient. In order to enhance the complexing ability of humic acid for metal ions, the present invention is modified based on demineralized low-quality coal. After strong acid corrosion, the pores of the substrate increase, the surface of the humic acid-based composite material becomes more complex and rough, the particle diameter increases, and more heterogeneous surfaces are presented, providing a large number of adsorption pores, and heavy metal ions are more easily adsorbed on the composite material. The reason is that oxygen-containing functional groups such as hydroxyl, carboxyl, epoxy, carbonyl, and lactone are recognized as important surface functional groups for adsorbing heavy metal ions, and can form organic combinations with heavy metal ions. After modification, the number of oxygen-containing functional groups on the surface of humic acid-based composite materials increased significantly, especially the phenol ether groups and carbon-carbon double bond aromatic bonds increased significantly, and the adsorption sites on the surface of the materials increased. The carboxyl and hydroxyl functional groups on the materials reacted with the heavy metal ions of Pb, Hg, and Cd, and the Pb, Hg, and Cd ions quickly occupied the adsorption sites provided on the surface of the humic acid-based composite materials. The reaction speed was extremely fast, and more metal ions could be adsorbed to form metal complexes. At the same time, heavy metal ions exchanged ions with oxygen-containing groups to form insoluble metal complexes, thereby reducing the accumulation of heavy metals by soil organisms. The synergistic polymer modified the surface of the material, and the humic acid composite repair material had a good solubilizing effect. When the humic acid composite repair material formed an organic-inorganic composite colloid with soil colloid particles, the material's adsorption capacity for organic matter was enhanced, and the content of organic pollutants in the soil decreased.
[0046] At the same time, with the increase in the amount of humic acid solution, the driving force of material adsorption is enhanced, and the effective groups are connected to the long chain, which expands the utilization rate of adsorption sites. However, if the amount of humic acid solution is too small, the active vacant sites on the surface of the humic acid-based composite material will be reduced, and metal ions will penetrate into the interior of the humic acid-based composite material and complex with the effective components, which will reduce the utilization rate of the adsorption sites.
[0047] The stability of soil aggregates reflects the water holding capacity, anti-erosion ability and permeability of its structure. When excessive humic acid composite remediation materials were added, the content of large aggregates in sand-grade soil was significantly reduced, soil aggregates were easily broken, and stability decreased. The content of Cd in the oxidized state of iron and manganese was significantly reduced, while the content of Cd in the ionic, weak organic and strong organic states increased, and the total detection amount of Cd changed little, indicating that excessive humic acid composite remediation materials caused the problem of reduced ability to remove heavy metal elements and poor mechanical stability of soil aggregates. At a certain dosage, the content of soil aggregates increased significantly with the increase of material particle size. However, humic acid composite remediation materials with too large particle size led to a significant increase in the content of micro-soil aggregates at the silt-grade level, and soil aggregates were easily broken and stability decreased. Moreover, different forms of Cd were enriched in micro-soil aggregates at the silt-grade level, and the Cd content of soil samples was relatively high. In summary, the addition of a small amount of humic acid composite remediation materials with moderate particle size is conducive to increasing the content of large aggregates in sand-grade soil, and this cementing material is conducive to enhancing soil water stability and moisture.
[0048] In addition, the oxidative functional groups such as phenolic hydroxyl and quinone in humic acid have a certain inhibitory effect on soil urease and nitrifying bacteria. Humic acid promotes the microorganisms and enzyme activities in the soil, promotes the increase in the number of aerobic bacteria, actinomycetes, and fiber decomposing bacteria, accelerates the mineralization of organic matter, and provides organic energy for soil microorganisms. As an electron acceptor for the respiration of microorganisms, humic acid can promote the growth and reproduction of microorganisms and population diversity, and effectively degrade soil organic pollutants.
[0049] The present invention is beneficial in that:
[0050] (1) The humic acid composite repair material of the present invention can effectively improve soil structure and quality;
[0051] (2) The humic acid composite remediation material of the present invention can effectively improve the efficiency of soil remediation. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0053] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0054] Example 1
[0055] A method for preparing a humic acid composite repair material for a coal chemical pollution site, the method comprising:
[0056] 1) 200 g lignite, 1 L of 0.1 mol / L NaOH solution, and 10 g of sodium pyrophosphate were mixed evenly, and the mixture was allowed to stand to obtain a supernatant and a solid. The supernatant was taken, and 200 mL of 0.5 mol / L HCl solution was added to adjust the pH value of the system. The humic acid solution was obtained after suction filtration;
[0057] 2) Drying step 1) The solid obtained by the operation is allowed to stand, and 5 mL of 1.5 mol / L HCl solution is added per gram of solid to mix evenly, and the product is washed with distilled water until it is neutral after filtering, and 5 mL of 40 wt% HF solution is added per gram of solid to corrode, and the product is filtered again, and the product is washed with distilled water until it is neutral, and the substrate is obtained after drying;
[0058] 3) Take acrylic acid and humic acid solution and mix them in a volume ratio of 1:0.5 to obtain a mixed solution. In addition, butyl acrylate, cyclohexane, tristearate sorbitan and acetone are prepared in a dosage ratio of 1g:0.26g:0.03g:15mL, and the temperature is raised to 50°C. While stirring, 0.05g of potassium persulfate is added to each gram of the mixture of butyl acrylate and cyclohexane. The mixture is kept at a constant temperature of 85°C for 3h. While hot, 1g of the base material is added to each gram of the organic raw material and the mixture is mixed evenly. After drying and grinding, the mixture is sieved through a 100-mesh sieve to obtain a humic acid composite repair material.
[0059] The soil from the coal chemical contaminated site was characterized, the soil moisture was maintained at 60%, the temperature was controlled at 20-25℃, and the concentration was 80g / m 2 The humic acid repair composite material of the present invention is evenly distributed, and the performance of the soil after repair for 60 days in a natural environment is tested. The specific testing method is as follows:
[0060] 1. Determination of heavy metal content in contaminated soil samples
[0061] Take 1g of the soil sample to be tested in a beaker, add 5mL of water to soak it, then add 30mL of HCl, heat and dry it on a hot plate, then add 10mL of HNO3 to the beaker, heat and dry it on a hot plate, add 10mL of HClO4 to the beaker and heat it on the hot plate until white smoke comes out, remove it and cool it, add 1mL of HNO3, dilute it to 5mL with water, take 3 colorimetric tubes, add the digested soil sample to the scale line, and determine the heavy metal content. Repeat the test three times in parallel. The Pb and Hg contents of the final sample are the average of the three parallel tests.
[0062] In addition, the cadmium ion content was determined by atomic absorption spectrophotometer, the weak organic binding state and strong organic binding state of Cd were determined by graphite furnace atomic absorption spectrophotometry, and other states were determined by flame atomic absorption spectrophotometry.
[0063] 2. Soil Aggregate Characterization
[0064] 1) Measure the particle size of soil aggregates by electron microscopy.
[0065] 2) Test the water stability using the hydrostatic method. Air-dry the soil sample to be tested, spray 2 mL of water on the surface of the aggregates per gram of the soil sample to be tested, and maintain at room temperature for 1 day to ensure that the water completely wets the soil sample. Re-sieve and select a volume of approximately 4 cm 3 Continue to add water, and start timing when the aggregate is completely immersed in water. Record the number of particles that collapse per minute within 10 minutes, and calculate the average of 3 groups. The formula for calculating the water stability of aggregates is as follows:
[0066] K=A×0.1+B×0.3+…+I×1.7+G×1.9+M×2.0
[0067] Where K is the water stability coefficient of the aggregate; A, B, …G are the number of particles that collapse per minute; and M is the number of particles that do not collapse after being immersed in water for 10 minutes.
[0068] The results are as follows.
[0069]
[0070] The embodiment of the present invention uses lignite, and the mass fraction of humin in the lignite exceeds 40wt%. After further purification, its mass fraction exceeds 90wt%. According to the results in the table, Hg in the exchangeable components and the reduced components combines with the humic acid composite repair material prepared in this example to form a poorly soluble, insoluble and stable complex, which can significantly reduce the effective content of Hg in the soil. The acid-treated humic acid composite repair material has a high porosity, which can enhance the ability to adsorb heavy metal ions, and the complex has a lower environmental migration ability and reduces biological impact, indicating that the product of this example can effectively improve the efficiency of soil remediation. At the same time, it can be seen that the soil sample after treatment forms large aggregates of sand-grade soil. In addition, as the amount of material added increases, the material and mineral small molecules can be cemented into soil aggregates with large particle size, forming a relatively stable cross-linked network structure, thereby making the soil water stability show a trend of gradually increasing. After a series of comparative experiments, the present invention determined that at 60 to 100 g / m 2 The product of the present invention has better effect when added in an amount of.
[0071] Example 2
[0072] A method for preparing a humic acid composite repair material for a coal chemical pollution site, the method comprising:
[0073] 1) 200 g lignite, 1 L of 0.1 mol / L NaOH solution, and 10 g of sodium pyrophosphate were mixed evenly, and the mixture was allowed to stand to obtain a supernatant and a solid. The supernatant was taken, and 200 mL of 0.5 mol / L HCl solution was added to adjust the pH value of the system. The humic acid solution was obtained after suction filtration;
[0074] 2) Drying step 1) The solid obtained by the operation is allowed to stand, and 5 mL of 1.5 mol / L HCl solution is added per gram of solid to mix evenly, and the product is washed with distilled water until it is neutral after filtering, and 5 mL of 40 wt% HF solution is added per gram of solid to corrode, and the product is filtered again, and the product is washed with distilled water until it is neutral, and the substrate is obtained after drying;
[0075] 3) Take acrylic acid and humic acid solution and mix them in a volume ratio of 1:0.5 to obtain a mixed solution. In addition, butyl acrylate, cyclohexane, tristearate sorbitan and acetone are prepared in a dosage ratio of 1g:0.26g:0.03g:15mL, and the temperature is raised to 50°C. While stirring, 0.05g of potassium persulfate is added to each gram of the mixture of butyl acrylate and cyclohexane. The mixture is kept at a constant temperature of 85°C for 3h. While hot, 1g of the base material is added to each gram of the organic raw material and the mixture is mixed evenly. After drying and grinding, the humic acid composite repair material is obtained through an 80-mesh sieve.
[0076] The soil from the coal chemical contaminated site was characterized, the soil moisture was maintained at 60%, the temperature was controlled at 20-25℃, and the concentration was 80g / m 2 The humic acid repair composite material of the present invention is evenly distributed in an amount, and the performance test of the soil after repair for 60 days in a natural environment is carried out in the same manner as in Example 1, and the results are as follows.
[0077]
[0078] According to the results in the table, at a certain dosage, the soil aggregate content increased significantly with the increase in material particle size, which obviously enhanced the water stability of the soil sample. The humic acid composite repair material in this example is rich in active groups, chelating with small molecules and complexing with metal ions, and the content of heavy metal ions is significantly reduced.
[0079] Example 3
[0080] A method for preparing a humic acid composite repair material for a coal chemical pollution site, the method comprising:
[0081] 1) 200 g lignite, 1 L of 0.1 mol / L NaOH solution, and 10 g of sodium pyrophosphate were mixed evenly, and the mixture was allowed to stand to obtain a supernatant and a solid. The supernatant was taken, and 200 mL of 0.5 mol / L HCl solution was added to adjust the pH value of the system. The humic acid solution was obtained after suction filtration;
[0082] 2) Drying step 1) The solid obtained by the operation is allowed to stand, and 5 mL of 1.5 mol / L HCl solution is added per gram of solid to mix evenly, and the product is washed with distilled water until it is neutral after filtering, and 5 mL of 40 wt% HF solution is added per gram of solid to corrode, and the product is filtered again, and the product is washed with distilled water until it is neutral, and the substrate is obtained after drying;
[0083] 3) Take acrylic acid and humic acid solution and mix them in a volume ratio of 1:0.5 to obtain a mixed solution. In addition, butyl acrylate, cyclohexane, tristearate sorbitan and acetone are prepared in a dosage ratio of 1g:0.26g:0.03g:15mL, and the temperature is raised to 50°C. While stirring, 0.05g of potassium persulfate is added to each gram of the mixture of butyl acrylate and cyclohexane. The mixture is kept at a constant temperature of 85°C for 3h. While hot, 1g of the base material is added to each gram of the organic raw material and the mixture is mixed evenly. After drying and grinding, the humic acid composite repair material is obtained by passing through a 60-mesh sieve.
[0084] The soil from the coal chemical contaminated site was characterized, the soil moisture was maintained at 60%, the temperature was controlled at 20-25℃, and the concentration was 80g / m 2 The humic acid repair composite material of the present invention is evenly distributed in an amount, and the performance test of the soil after repair for 60 days in a natural environment is carried out in the same manner as in Example 1, and the results are as follows.
[0085]
[0086] According to the results in the table, the humic acid composite repair material with a larger particle size significantly increases the content of micro-soil aggregates at the silt grain level, the soil aggregates are easily broken, and the water stability shows a downward trend. At the same time, combined with Example 2 and Example 3, it can be analyzed that the Cd content of the soil sample is relatively high because different forms of Cd are enriched in micro-soil aggregates at the silt grain level. Combined with the results of Examples 1 to 3, the present invention should add a small amount of humic acid composite repair material with a moderate particle size, which is beneficial to increase the content of large aggregates of sand-grade soil. This cementitious substance is beneficial to enhance the water stability and humidity of the soil.
[0087] Example 4
[0088] A method for preparing a humic acid composite repair material for a coal chemical pollution site, the method comprising:
[0089] 1) Take 200g of peat, 1L of 0.1mol / L NaOH solution, and 10g of sodium pyrophosphate and mix them evenly. After standing, obtain a supernatant and a solid. Take the supernatant, add 200mL of 0.5mol / L HCl solution to adjust the pH value of the system, and obtain a humic acid solution after suction filtration;
[0090] 2) Drying step 1) The solid obtained by the operation is allowed to stand, and 5 mL of 1.5 mol / L HCl solution is added per gram of solid to mix evenly, and the product is washed with distilled water until it is neutral after filtering, and 5 mL of 40 wt% HF solution is added per gram of solid to corrode, and the product is filtered again, and the product is washed with distilled water until it is neutral, and the substrate is obtained after drying;
[0091] 3) Take acrylic acid and humic acid solution and mix them in a volume ratio of 1:0.5 to obtain a mixed solution. In addition, butyl acrylate, cyclohexane, tristearate sorbitan and acetone are prepared in a dosage ratio of 1g:0.26g:0.03g:15mL, and the temperature is raised to 50°C. While stirring, 0.05g of potassium persulfate is added to each gram of the mixture of butyl acrylate and cyclohexane. The mixture is kept at a constant temperature of 85°C for 3h. While hot, 1g of the base material is added to each gram of the organic raw material and the mixture is mixed evenly. After drying and grinding, the humic acid composite repair material is obtained through an 80-mesh sieve.
[0092] The soil from the coal chemical contaminated site was characterized, the soil moisture was maintained at 60%, the temperature was controlled at 20-25℃, and the concentration was 80g / m 2 The humic acid repair composite material of the present invention is evenly distributed in an amount, and the performance test of the soil after repair for 60 days in a natural environment is carried out in the same manner as in Example 1, and the results are as follows.
[0093]
[0094] According to the results in the table, combined with Example 2, it can be analyzed that the composite repair material prepared by extracting humin from lignite in the present invention has a strong adsorption and passivation effect on heavy metal cadmium.
[0095] Comparative Example 1
[0096] A method for preparing a humic acid composite repair material for a coal chemical industry polluted site, the method comprising:
[0097] 1) 200 g lignite and 1 L of 0.1 mol / L NaOH solution were mixed evenly, and the mixture was allowed to stand to obtain a supernatant and a solid. The supernatant was taken, and 200 mL of 0.5 mol / L HCl solution was added to adjust the pH value of the system. The humic acid solution was obtained by suction filtration;
[0098] 2) Drying step 1) The solid obtained by the operation is allowed to stand, and 5 mL of 1.5 mol / L HCl solution is added per gram of solid to mix evenly, and the product is washed with distilled water until it is neutral after filtering, and 5 mL of 40 wt% HF solution is added per gram of solid to corrode, and the product is filtered again, and the product is washed with distilled water until it is neutral, and the substrate is obtained after drying;
[0099] 3) Take acrylic acid and humic acid solution and mix them in a volume ratio of 1:0.5 to obtain a mixed solution. In addition, butyl acrylate, cyclohexane, tristearate sorbitan and acetone are prepared in a dosage ratio of 1g:0.26g:0.03g:15mL, and the temperature is raised to 50°C. While stirring, 0.05g of potassium persulfate is added to each gram of the mixture of butyl acrylate and cyclohexane. The mixture is kept at a constant temperature of 85°C for 3h. While hot, 1g of the base material is added to each gram of the organic raw material and the mixture is mixed evenly. After drying and grinding, the humic acid composite repair material is obtained through an 80-mesh sieve.
[0100] The soil from the coal chemical contaminated site was characterized, the soil moisture was maintained at 60%, the temperature was controlled at 20-25℃, and the concentration was 80g / m 2 The humic acid repair composite material of the present invention is evenly distributed in an amount, and the performance test of the soil after repair for 60 days in a natural environment is carried out in the same manner as in Example 1, and the results are as follows.
[0101]
[0102] The present invention firstly obtains humic acid (palmitic humic acid), fulvic acid, etc. rich in functional groups such as carbonyl, carboxyl, and ether oxygen groups by leaching with dilute alkali solution and acid solution-assisted precipitation. The water-insoluble and water-soluble combined humic acid is complexed into water-soluble humic acid salts, which are coordinated with sodium pyrophosphate to significantly increase the humic acid extraction amount. In Example 2, the humic acid extraction amount is 17.2wt%, and the purity is far higher than that of commercially available humic acid repair materials. According to the results in the table, combined with the characterization results, the humic acid extraction amount is only 8.4wt%, which obviously causes a significant decrease in the ability of the material to remove heavy metals.
[0103] The above test was also performed with the exception of replacing the HCl solution used in this example with a dilute sulfuric acid solution. According to the results in the table, since the solution is rich in divalent metal ions, precipitation will form, reducing the purity of the humic acid product and significantly reducing the material's ability to remove heavy metals.
[0104] Comparative Example 2
[0105] A method for preparing a humic acid composite repair material for a coal chemical pollution site, the method comprising:
[0106] 1) Take 200g lignite, 1L NaOH solution with a concentration of 0.1mol / L, and 10g sodium pyrophosphate, mix them evenly, let them stand to obtain a supernatant and a solid, take the supernatant, add 200mL HNO3 solution with a concentration of 0.5mol / L to adjust the pH value of the system, and obtain a humic acid solution after suction filtration;
[0107] 2) Drying step 1) The solid obtained by the operation is allowed to stand, and 5 mL of 1.5 mol / L HCl solution is added per gram of solid to mix evenly, and the product is washed with distilled water until it is neutral after filtering, and 5 mL of 40 wt% HF solution is added per gram of solid to corrode, and the product is filtered again, and the product is washed with distilled water until it is neutral, and the substrate is obtained after drying;
[0108] 3) Take acrylic acid and humic acid solution and mix them in a volume ratio of 1:0.5 to obtain a mixed solution. In addition, butyl acrylate, cyclohexane, tristearate sorbitan and acetone are prepared in a dosage ratio of 1g:0.26g:0.03g:15mL, and the temperature is raised to 50°C. While stirring, 0.05g of potassium persulfate is added to each gram of the mixture of butyl acrylate and cyclohexane. The mixture is kept at a constant temperature of 85°C for 3h. While hot, 1g of the base material is added to each gram of the organic raw material and the mixture is mixed evenly. After drying and grinding, the humic acid composite repair material is obtained through an 80-mesh sieve.
[0109] The soil from the coal chemical contaminated site was characterized, the soil moisture was maintained at 60%, the temperature was controlled at 20-25℃, and the concentration was 80g / m 2 The humic acid repair composite material of the present invention is evenly distributed in an amount, and the performance test of the soil after repair for 60 days in a natural environment is carried out in the same manner as in Example 1, and the results are as follows.
[0110]
[0111]
[0112] Considering that the cation of substances such as sodium pyrophosphate is sodium, this example uses NaOH solution for alkaline solution dissolution. This experiment uses "NaOH solution dissolution and HNO3 solution precipitation". Since HNO3 solution has a strong oxidizing effect and can react with functional groups, the humic acid macromolecules are degraded into small molecules. According to the results in the table, the particle size of the soil sample after treatment is small and its water stability is poor.
[0113] Comparative Example 3
[0114] A method for preparing a humic acid composite repair material for a coal chemical pollution site, the method comprising:
[0115] 1) 200 g lignite, 1 L of 0.1 mol / L NaOH solution, and 10 g of sodium pyrophosphate were mixed evenly, and the mixture was allowed to stand to obtain a supernatant and a solid. The supernatant was taken, and 200 mL of 0.5 mol / L HCl solution was added to adjust the pH value of the system. The humic acid solution was obtained after suction filtration;
[0116] 2) Drying step 1) The solid obtained by the operation is allowed to stand, and 5 mL of 1.5 mol / L HCl solution is added per gram of solid to mix evenly, and the product is washed with distilled water until it is neutral after filtering, and 5 mL of 40 wt% HF solution is added per gram of solid to corrode, and the product is filtered again, and the product is washed with distilled water until it is neutral, and the substrate is obtained after drying;
[0117] 3) Take acrylic acid and humic acid solution and mix them evenly in a volume ratio of 1:0.5 to obtain a mixed solution. In addition, butyl acrylate, tristearate sorbitan and acetone are prepared in a dosage ratio of 1g:0.03g:15mL, and the temperature is raised to 50°C. While stirring, 0.05g of potassium persulfate is added to the mixed solution per gram of butyl acrylate. The mixture is kept at a constant temperature of 85°C for 3h. While hot, 1g of base material is added per gram of organic raw material and mixed evenly. After drying, grinding and passing through an 80-mesh sieve, a humic acid composite repair material is obtained.
[0118] The soil from the coal chemical contaminated site was characterized, the soil moisture was maintained at 60%, the temperature was controlled at 20-25℃, and the concentration was 80g / m 2 The humic acid repair composite material of the present invention is evenly distributed in an amount, and the performance test of the soil after repair for 60 days in a natural environment is carried out in the same manner as in Example 1, and the results are as follows.
[0119]
[0120] Oxygen-containing functional groups such as epoxy groups are considered to be important surface functional groups for adsorbing heavy metal ions, and can form organic combinations with heavy metal ions. According to the results in the table, since the number of oxygen-containing functional groups on the surface of the humic acid-based composite material in this example is lower than that in Example 2, there are fewer adsorption sites. Pb, Hg, and Cd ions quickly occupy the adsorption sites provided on the surface of the humic acid-based composite material to form insoluble metal complexes, which reduces the accumulation of heavy metals by soil organisms, but the effect is not as good as that of the material in Example 2.
[0121] Moreover, judging from the above results, the actual adsorption effect on Cd is significantly weakened. This is because the ring structure modification is introduced in the technical solution of the present invention, which changes the adsorption site of Cd and significantly improves its adsorption capacity and adsorption amount.
[0122] Comparative Example 4
[0123] A method for preparing a humic acid composite repair material for a coal chemical pollution site, the method comprising:
[0124] 1) 200 g lignite, 1 L of 0.1 mol / L NaOH solution, and 10 g of sodium pyrophosphate were mixed evenly, and the mixture was allowed to stand to obtain a supernatant and a solid. The supernatant was taken, and 200 mL of 0.5 mol / L HCl solution was added to adjust the pH value of the system. The humic acid solution was obtained after suction filtration;
[0125] 2) Drying step 1) The solid obtained by the operation is allowed to stand, and 5 mL of 1.5 mol / L HCl solution is added per gram of solid to mix evenly, and the product is washed with distilled water until it is neutral after filtering, and 5 mL of 40 wt% HF solution is added per gram of solid to corrode, and the product is filtered again, and the product is washed with distilled water until it is neutral, and the substrate is obtained after drying;
[0126] 3) Take acrylic acid and humic acid solution in a volume ratio of 1:1 and mix them evenly to obtain a mixed solution. In addition, butyl acrylate, cyclohexane, tristearate sorbitan and acetone are prepared in a dosage ratio of 1g:0.26g:0.03g:15mL, and the temperature is raised to 50°C. While stirring, 0.05g of potassium persulfate is added to each gram of the mixture of butyl acrylate and cyclohexane. The mixture is kept at a constant temperature of 85°C for 3h. While hot, 1g of the base material is added to each gram of the organic raw material and the mixture is evenly mixed. After drying and grinding, the humic acid composite repair material is obtained by passing through an 80-mesh sieve.
[0127] The soil from the coal chemical contaminated site was characterized, the soil moisture was maintained at 60%, the temperature was controlled at 20-25℃, and the concentration was 80g / m 2 The humic acid repair composite material of the present invention is evenly distributed in an amount, and the performance test of the soil after repair for 60 days in a natural environment is carried out in the same manner as in Example 1, and the results are as follows.
[0128]
[0129] Through a series of experiments, we know that with the increase of the amount of humic acid solution, the material adsorption driving force is enhanced, the effective groups are connected to the long chain, and the utilization rate of the adsorption site is expanded. However, if the amount of humic acid solution is too small, the surface active vacant sites of the humic acid-based composite material will be reduced, and the metal ions will penetrate into the interior of the humic acid-based composite material and complex with the effective components, which will reduce the utilization rate of the adsorption site. According to the results in the table, the material's ability to remove heavy metals is significantly reduced.
[0130] Comparative Example 5
[0131] A method for preparing a humic acid composite repair material for a coal chemical pollution site, the method comprising:
[0132] 1) 200 g lignite, 1 L of 0.1 mol / L NaOH solution, and 10 g of sodium pyrophosphate were mixed evenly, and the mixture was allowed to stand to obtain a supernatant and a solid. The supernatant was taken, and 200 mL of 0.5 mol / L HCl solution was added to adjust the pH value of the system. The humic acid solution was obtained after suction filtration;
[0133] 2) Drying step 1) The solid obtained by the operation is allowed to stand, and 5 mL of 1.5 mol / L HCl solution is added per gram of solid to mix evenly, and the product is washed with distilled water until it is neutral after filtering, and 5 mL of 40 wt% HF solution is added per gram of solid to corrode, and the product is filtered again, and the product is washed with distilled water until it is neutral, and the substrate is obtained after drying;
[0134] 3) Take acrylic acid and humic acid solution and mix them in a volume ratio of 1:0.5 to obtain a mixed solution. In addition, butyl acrylate, cyclohexane, tristearate sorbitan and acetone are prepared in a dosage ratio of 1g:0.26g:0.03g:15mL, and the temperature is raised to 50°C. While stirring, 0.05g of potassium persulfate is added to each gram of the mixture of butyl acrylate and cyclohexane. The mixture is kept at a constant temperature of 85°C for 3h. While hot, 1g of the base material is added to each gram of the organic raw material and the mixture is mixed evenly. After drying and grinding, the humic acid composite repair material is obtained through an 80-mesh sieve.
[0135] The soil from the coal chemical contaminated site was characterized, the soil moisture was maintained at 60%, the temperature was controlled at 20-25°C, and the concentration of 120 g / m 2 The humic acid repair composite material of the present invention is evenly distributed in an amount, and the performance test of the soil after repair for 60 days in a natural environment is carried out in the same manner as in Example 1, and the results are as follows.
[0136]
[0137] According to the results in the table, when excessive amounts of humic acid composite remediation materials are added, the content of large aggregates in sand-grade soil is significantly reduced, soil aggregates are easily broken, and stability decreases. The content of Cd in the ferromanganese oxidation state is significantly reduced, the content of Cd in the ionic, weak organic, and strong organic states increases, and the total amount of Cd detected changes little. Excessive amounts of humic acid composite remediation materials, on the contrary, cause the ability to remove heavy metal elements to decrease and the mechanical stability of soil aggregates to deteriorate. This is mainly because the mobility of the remediation material in the contaminated soil has changed, causing it to form aggregates or precipitation forms, and the degree of binding with the soil decreases, especially having a great impact on the binding form of Cd.
Claims
1. A method for preparing a humic acid composite repair material for coal chemical pollution sites, characterized in that: The method comprises: 1) Mix the raw materials, alkali solution and phosphide evenly, take the supernatant after standing, add acid solution to adjust the pH value of the system, and obtain humic acid solution by suction filtration; 2) Drying step 1) The solid obtained by the operation is allowed to stand, an acid solution is added to mix evenly, filtered, washed, corroded by adding a strong acid, filtered again, washed, and dried to obtain a substrate; 3) The organic raw material, emulsifier and solvent are heated, and while stirring, a mixture of acyclic carboxylic acid and humic acid solution is added, and an initiator is added. After a thermal reaction, the base material is added while hot and mixed evenly, and the humic acid composite repair material is obtained after drying and grinding.
2. The method for preparing a humic acid composite repair material for coal chemical pollution sites according to claim 1, characterized in that: Step 1) The raw material is low-quality coal; The low-quality coal is lignite and / or weathered coal and / or coal; The alkali solution is a 0.1-0.5 mol / L NaOH aqueous solution, and its dosage is 5.0-10.0 mL / g raw material; The phosphide is sodium pyrophosphate, and its usage is 0.05-0.10 g / g raw material.
3. The method for preparing a humic acid composite repair material for coal chemical pollution sites according to claim 1 or 2, characterized in that: Step 1) The acid solution is a 0.1-0.5 mol / L HCl aqueous solution, and its dosage is 1.0-1.5 mL / g raw material.
4. The method for preparing a humic acid composite repair material for coal chemical pollution sites according to claim 1, characterized in that: Step 2) The cleaning is to wash the product with distilled water until it is neutral; Step 2) The strong acid is a 35-45 wt% HF aqueous solution, and the amount used is 5-10 mL / g of the solid obtained in step 1).
5. The method for preparing a humic acid composite repair material for coal chemical pollution sites according to claim 1, characterized in that: Step 3) the organic raw materials are butyl acrylate and cyclohexane; The mass ratio of butyl acrylate to cyclohexane is 1:(0.2-0.3); The emulsifier is sorbitan tristearate, and its dosage is 0.01-0.05 g / g organic raw material; The solvent is acetone, and the amount thereof is 15 to 25 mL / g of organic raw material; Step 3) The temperature is raised to 50-60°C.
6. The method for preparing a humic acid composite repair material for coal chemical pollution sites according to claim 1, characterized in that: Step 3) in the mixture of the acyclic carboxylic acid and the humic acid solution: The acyclic carboxylic acid is acrylic acid; The acyclic carboxylic acid and humic acid solution are prepared in a volume ratio of 1: (0.5-0.7) and mixed evenly.
7. The method for preparing a humic acid composite repair material for coal chemical pollution sites according to claim 1, characterized in that: Step 3) The initiator is potassium persulfate, and the amount thereof is 0.05-0.1 g / g organic raw material; Step 3) The thermal reaction is carried out at 80-90°C for 2-5 hours.
8. The method for preparing a humic acid composite repair material for coal chemical pollution sites according to claim 1 or 7, characterized in that: Step 3) The substrate is added in an amount of 0.9 to 1.1 g per gram of organic raw material.
9. The method for preparing a humic acid composite repair material for coal chemical pollution sites according to claim 1, characterized in that: Step 3) The grinding is followed by passing through a 60-100 mesh sieve.
10. A humic acid composite repair material for coal chemical contaminated sites prepared by the method of any one of claims 1 to 9.
Citation Information
Patent Citations
Method for extracting high-purity humic acid from low-rank coal
CN102558573A
Magnetic recyclable soil heavy metal absorbent and preparation method thereof
CN107552009A
Method for preparing weathered coal humic acid-based super absorbent resin by using water solution polymerizing method
CN107722196A
Preparation method, use method and application of humic acid aqueous solution
CN109111578A
Method for extracting humic acid from mineral source
CN112812323A
Cited By
In-situ microbial remediation method for heavy metal polluted site of in-production enterprise
CN120347057A